Business and public health impacts of a food safety rating program among pork vendors in Vietnam - Murphy, Mike; Dang-Xuan, Sinh; Hoffmann, Vivian; Le-Thi-Huyen, Trang; Unger, Fred; Pham-Thi, Huong; Nguyen-Quang, Duy; Nguyen-Viet, Hung (International Food Policy Research Institute, 2024)
Pork is the most widely consumed meat in Vietnam (OECD, 2023), where traditional food markets typically lacking refrigeration account for 84% of retail trade (USDA, 2024). Previous research by the International Livestock Research Institute (ILRI) and its partners found that over 60% of meat samples collected from such markets were contaminated with Salmonella (Ngo et al., 2023). This situation is typical of food markets in low and middle-income countries, where foodborne illness is estimated to claim 420,000 lives (Havelaar, et al., 2015) and cause a productivity loss of US$95 billion annually (Jaffee, Henson, Unnevehr, Grace, & Cassou, 2019). Adherence to basic food and hand hygiene practices among meat vendors has the potential to reduce contamination cost-effectively, but would require either market incentives or regulatory enforcement, both of which are often absent in traditional markets. Punitive approaches to enforcement of food safety standards can backfire – for example, vendors may evade regulators by moving to informal markets that lack access to even basic water infrastructure. Further, shutting down non-compliant vendors could reduce access to nutritious foods among low-income consumers.